2010
DOI: 10.1038/jhg.2010.91
|View full text |Cite
|
Sign up to set email alerts
|

Myocilin and optineurin coding variants in Hispanics of Mexican descent with POAG

Abstract: Coding variants in both myocilin (MYOC) and optineurin (OPTN) are reported risk factors for primary open-angle glaucoma (POAG) in many populations. This study investigated the contribution of MYOC and OPTN coding variants in Hispanics of Mexican descent with and without POAG. We conducted a case/control study of unrelated POAG cases and non-glaucomatous controls in a population of Hispanics of Mexican descent. Ascertainment criteria for POAG included the presence of glaucomatous optic neuropathy with associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In fact, associations between the GSTM1 null polymorphism has also been associated with POAG in Brazilian populations [ 101 , 120 , 121 ]. Meanwhile, MYOC and OPTN polymorphisms have shown no association [ 122 ], although MYOC variants studied in Peruvian populations have shown both novel and previously reported genetic variants from other populations [ 123 , 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, associations between the GSTM1 null polymorphism has also been associated with POAG in Brazilian populations [ 101 , 120 , 121 ]. Meanwhile, MYOC and OPTN polymorphisms have shown no association [ 122 ], although MYOC variants studied in Peruvian populations have shown both novel and previously reported genetic variants from other populations [ 123 , 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…171 Cells developed special mechanisms to remove DNA damage and 173 OPTN is the second gene identified by genetic linkage analysis, which may be responsible for approximately 1.5% of NTG cases. 174 It was reported that OPTN protects cells from oxidative stress and inhibits cytochrome c release from mitochondria. 175 Vitamin C is an important water-soluble antioxidant.…”
Section: Oxidative Stress-related Genesmentioning
confidence: 99%
“…9,46 Subsequently, most studies of optineurin in large populations of glaucoma patients have suggested that mutations in this gene may be responsible for up to 1.5% of NTG cases. [47][48][49] The strongest data linking mutations in optineurin with glaucoma are focused on the GLU50LYS mutation. The links between other optineurin mutations and glaucoma are more complex, as these mutations are associated with glaucoma in some but not all populations.…”
Section: Myocilin (Myoc Omim #601652)mentioning
confidence: 99%